Application of fluorescent In situ hybridization for rapid detection of aggregatibacter actinomycetemcomitans in patients with chronic periodontitis - Kishore G Bhat; Aaradhana Chhatre; Vijay M Kumbar; Manohar S Kugaji; Sanjeevani Patil (Wolters Kluwer Medknow Publications, 2018)
Background: Aggregatibacter actinomycetemcomitans is a proven periodontal pathogen. In dentistry, there is a need to identify and quantitate the organisms from the diseased sites quickly and reliably. Since culture requires several days, molecular methods are being used frequently to detect A. actinomycetemcomitans. Among them, fluorescent in situ hybridization (FISH) is rapid, sensitive and quantitative. An attempt is made here to evaluate the applicability of this technique as a diagnostic tool in periodontology. Materials and Methods: A total of 77 healthy individuals and 77 patients with chronic periodontitis were enrolled for the study. Subgingival plaque was collected, fixed with paraformaldehyde and subjected to FISH. Oligonucleotide probe labelled with 6-carboxyfluorescein (FAM) was used for hybridization. After the procedure, the fluorescently stained A. actinomycetemcomitans were identified and counted from the smear and quantitated using a simple grading. Results: The data revealed that plaques from 84.5% of healthy individuals and 98.7% of chronic periodontitis showed the presence of A. actinomycetemcomitans. However, the number of these bacteria were very low in most positive samples from healthy subjects in contrast to patients with chronic periodontitis, who had higher number of organisms. Statistical analysis using Mann-Whitney test revealed a significant difference among the two groups with P ≤ 0.001 and Z = −5.833. Conclusions: The procedure used in the study is simple, rapid and can be easily adaptable. It also has a high sensitivity and has the ability to detect a single bacterial cell. The method can be directly applied to the clinical samples and can be used as a rapid diagnostic tool in periodontics.